Can eco-routing, eco-driving and eco-charging contribute to the European Green Deal? Case Study: The City of Alcalá de Henares (Madrid, Spain). (1st August 2021) - Ortega-Cabezas, Pedro-Miguel; Colmenar-Santos, Antonio; Borge-Diez, David; Blanes-Peiró, Jorge-Juan
Abstract: The European Green Deal aims to make Europe the first climate-neutral continent and reduce greenhouse gas emissions by 2050. This research offers proposals for the European Green Deal based on sustainable transport, clean energy and reduction in the energy consumption of buildings. An algorithm based on the Here® application programming interface, neural networks, data from the Spanish transmission system operator, eco-routing, eco-driving and eco-charging is proposed. Its contribution to vehicle-to-home, renewable energy integration, and vehicle-to-home and vehicle-to-grid compatibility is analysed by using data acquisitions of the trips made by drivers from different social groups. The algorithm allows a daily energy saving of up to 2.2 kWh for freelancers, 1.5 kWh for commuters and 0.6 kWh for local workers. The vehicle-to-home contribution increases from 18 MWh to 553 MWh per year. Finally, neural networks allow better integration of renewable energy. The contributions to the European Green Deal are as follows: energy efficiency improves when policies are addressed to the adequate social sector combined with eco-driving and eco-routing; neural networks allow for achieving a better integration of renewable energies as they can predict when its contribution is higher; and policies to make vehicle-to-grid and vehicle-to-home compatible with reduced emissions must be developed. Highlights: Eco-driving, eco-routing and eco-charging contribution to energy efficiency. – Neural networks and stochastic usage of electric vehicles. – European green deal and stochastic electric mobility. Electric mobility and neural networks.